Hilbert problem with measurable data for semilinear equations of the Vekua type - Gutlyanskiĭ, V.Ya.; Nesmelova, O.V.; Ryazanov, V.I.; Yefimushkin, A.S. (Доповіді НАН України, 2022)
We prove the existence of solutions for the Hilbert boundary-value problem with arbitrary measurable data for the
nonlinear equations of the Vekua’s type ∂Z̅̄f(z) = h(z)q(f(z)). The found solutions differ from the classical ones,
because our approach is based on the notion of boundary values in the sense of angular limits along nontangential paths.
The results obtained can be applied to the establishment of existence theorems for the Poincaré and Neumann
boundary-value problems for the nonlinear Poisson equations of the form ΔU(z) = H(z)Q(U (z )) with arbitrary
measurable boundary data with respect to the logarithmic capacity. They can be also applied to the study of some
semilinear equations of mathematical physics modeling such processes as the diffusion with absorption, plasma
states, stationary burning etc. in anisotropic and inhomogeneous media. Дана робота містить теореми існування розв’язків граничної задачі Гільберта з довільними вимірними даними для відповідних нелінійних рівнянь типу Векуа ∂Z̅̄f(z) = h(z)q(f(z)). Знайдені розв’язки не є
класичними, оскільки наш підхід базується на інтерпретації граничних значень у сенсі кутових (вздовж
недотичних шляхів) границь, що є традиційним інструментом геометричної теорії функцій, але не рівнянь
у частинних похідних. Одержані результати можуть бути застосовані до встановлення теорем існування
для граничної задачі Пуанкаре і, зокрема, для задачі Неймана для нелінійних рівнянь Пуасона виду
ΔU(z) = H(z)Q(U(z)) з довільними вимірними даними відносно логарифмічної ємності. Таким чином, вони
можуть буть застосовані також до напівлінійних рівнянь математичної фізики під час моделювання різних
фізичних процесів, таких як дифузія з абсорбцією, стани плазми, стаціонарне горіння і т. д. в анізотропних
і неоднорідних середовищах. Останнє буде змістом наших подальших статей.